Strategies of adults for dealing with feelings of guilt – findings from a large web-based survey - Tobias Luck; Claudia Luck-Sikorski (Health Psychology Report, 2022)
Background Feelings of guilt are common in adulthood. Depending on the situation, individuals need different strategies for dealing with these usually unpleasant experiences. The aim of this study was to provide comprehensive empirical information about such different guilt-related strategies used in adulthood.